Seismic performance to cable stayed bridge under different earthquake loadings - Muhammad Aimran Amzar, Kamarudin (2019)
The paper deals with the seismic analysis of a stayed cable bridge structure in Malaysia with the aim to compute the response and assess the resistance capacity of the structure under different earthquake loading. Nevertheless, the border state of the stayed cable is assumed as fixed to the ground and type of soil has been neglected. The study was conducted because the tremors in Malaysia were due to the seismic wave generated from the earthquake that occurred in neighbouring countries. Therefore, engineers are concerned about the seismic vulnerability of bridge structures due to lack of earthquake consideration in Malaysia's building design procedure. Bridge structure is the critical structure that will damage cause by the seismic effect and also important component in transportation system. With this, stayed cable bridge is modelled and analysed using Finite Element Modelling(FEM) by SAP2000 software under various type of analysis that cover Free Vibration Analysis (FVA) and Time History Analysis (THA) under the different earthquake loading. Auto wind load in SAP2000 has been used in both analyses. The earthquake loading data is taking from Acheh and El-Centro earthquake that had been record by Malaysia Meteorological Department. Implementation between two type of different earthquake loading will represent the contrasting of dynamic characteristic of bridge structure. Furthermore, the overall seismic performance of stayed cable bridge significantly enhanced in longitudinal and transverse directions. It can summarize that the design of the stayed cable bridge is stable and ability to withstand under major and minor earthquake and also can yield adequate resistance against different earthquake loading.